Comparative analysis of phenotypic and genotypic antibiotic susceptibility patterns in Mycobacterium avium complex. (April 2020) - Wetzstein, Nils; Kohl, Thomas A.; Andres, Sönke; Schultze, Tilman G.; Geil, Ari; Kim, Eunhee; Biciusca, Teodora; Hügel, Christian; Hogardt, Michael; Lehn, Annette; Vehreschild, Maria J.G.T.; Wolf, Timo; et al.
Highlights: Macrolide resistance is a rare event in clinical specimens of M. avium complex. Results of phenotypic drug susceptibility testing have to be considered with care due to impaired stability in rifampicin, doxycyclin and rifabutin. pDST and gDST results should be combined in order to guide antimicrobial therapy in NTM. Changes in susceptibility can be linked to mutation within the same strain, but reinfection is frequent. Abstract: Objective: Phenotypic (Sensititre Myco, pDST) and genotypic drug susceptibility testing (GenoType NTM DR, gDST) in M. avium complex (MAC) have become available as standardized assays, but comparable data is needed. This study aimed to investigate the phenotypic and genotypic drug susceptibility patterns in MAC clinical isolates. Methods: Overall, 98 isolates from 85 patients were included. pDST and gDST were performed on all isolates and results compared regarding specificity and sensitivity using pDST as a reference method. The impact of drug instability on pDST results was studied using a biological assay over 14 days. In addition, the evolution of antimicrobial resistance was investigated in sequential isolates of 13 patients. Results: Macrolide resistance was rare, 1.2% (95% CI 0.7–7.3) of isolates in the base cohort. No aminoglycoside resistances were found, but 14.1% of the studied isolates (95% CI 7.8–23.8) showed intermediate susceptibility. The GenoType NTM DR identified two out of four macrolide-resistant isolates. Antibiotic stability was demonstrated to be poor in rifampicin, rifabutin, and doxycycylin. Conclusions: pDST results in NTM for unstable antibiotics must be interpreted with care. A combination of pDST and gDST will be useful for the guidance of antimicrobial therapy in MAC-disease.